Approaches to the Humanitarian Crisis in the Middle East - Verano, Martha Guadalupe G. (Revista Tribuna Internacional, 2016)
The violation of the human rights of persons is the fundamental cause for refuge seeking and displacement. This is so, given that the fear of incarceration, torture, slavery, rape or murder is the driving force leading people to flee, leaving behind their homes, communities and country of origin. The present article is derived of the doctorate thesis investigation and it’s propose is to give an approximation to the problematic of whom leave their home for became into refugees. The refugee problem has worsened because of the armed conflicts in different places around the world, like in the Middle East, especially in Syria.